2011
DOI: 10.1111/j.1472-765x.2011.03149.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the inhibitory effect of copper sulfate on the growth of Penicillium expansum and Botrytis cinerea

Abstract: Aims:  This study aimed to investigate the effect of copper sulfate (from 0 to 8 mmol kg−1) on radial growth rate and lag time of two moulds responsible for vine grapes spoilage: Penicillium expansum strain 25·03 and Botrytis cinerea, strains BC1 and BC2. Methods and results:  A new model was developed to describe tailing and shoulders in the inhibition curves. Because of tailing, the minimum inhibitory concentration (MIC), was not defined as the concentration at which no growth was observed, but as the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…That is in accordance with the fact that yeasts, especially C. albicans, are more resistant to high concentrations of copper than other species [46,47]. On the other hand, it is well known that Cu(II) ions inhibit mould growing [48][49][50]. The mechanism of action includes strong Cu 2+ bonding with the amino groups of chitin and chitosane of the mould cell walls, wherein their normal growth is interrupted [51].…”
Section: Antimicrobial Activitymentioning
confidence: 52%
“…That is in accordance with the fact that yeasts, especially C. albicans, are more resistant to high concentrations of copper than other species [46,47]. On the other hand, it is well known that Cu(II) ions inhibit mould growing [48][49][50]. The mechanism of action includes strong Cu 2+ bonding with the amino groups of chitin and chitosane of the mould cell walls, wherein their normal growth is interrupted [51].…”
Section: Antimicrobial Activitymentioning
confidence: 52%
“…Accordingly, Weaver et al (2010) reported on the sensitivity of several strains of Fusarium, Penicillium and Aspergillus to a copper surface, and found resilient spores of Aspergillus niger. Judet-Correia et al (2011) reported minimal inhibitory concentrations of copper sulphate of about 4.7 mmol kg −1 for P. expansum, and around 8 mmol kg −1 for B. cinerea, demonstrating also that some isolates are resistant to copper. Relevant strain specificities or matrix characteristics have not been fully identified, and consequently provide controversial results.…”
Section: Antimicrobial Activity Against Spoilage-related Microorganismentioning
confidence: 94%
“…Methods C and D released amounts of copper close to the detection limit of the system in water (below 100 ppm). According to Judet-Correia et al (2011), concentrations above 4 mmol kg −1 of copper sulphate are sufficient to inactivate Penicillium expansum and some isolates of Botrytis cinerea, consequently the methods A and B are expected to produce concentrations with antifungal activity. Fig.…”
Section: Characterization Of Colloidal Solutions and Migration Of Copmentioning
confidence: 99%
“…To prevent these kinds of food from mold spoilage, manufacturers should take into consideration in their pasteurization processes the D-values and z-values either of the actual contaminants or of a model. B. fulva is a good model candidate because it has been 3, 31,32,71,72,75,83,109,111,127,128 Linear 5, 13,14,18,21,44,47,51,52,57,58,60,80,85,87,88,90,110,114,115 Two-phase linear (eq. 5)…”
Section: Process and Environmental Factors Influencing Mold Growthmentioning
confidence: 99%
“…The general pattern of this model is flexible; it allows inclusion of a large set of mathematical expressions for each gamma term ( Table 3) and addition of new gamma tenns, for example to describe the effect of an inhibitory compound (52).…”
Section: Mathematical Models Quantifying the Influence Of Formulationmentioning
confidence: 99%